Numerical model for the simulation of soil water flow under root absorption conditions - Ángel del Vigo García; Luis Juana Sirgado; Leonor Rodríguez-Sinobas (Ingeniería del Agua)
An explicit finite differences routine was developed to simulate three-dimensional water flow from trickle irrigation under unsaturated non-stationary conditions; the code was validated by comparison with analytical solutions, other existing numerical models and laboratory experiments. Recently, the model was improved in order to reproduce flow root absorption via a time dependent macroscopic approach. This work presents the numerical model subroutine for root absorption and some results obtained by the model.